Structure of feeding for Echinarachnius parma and Scaphechinus mirabilis (Echinoidea, Clypeasteroida) in the Troitsa Bay, Japan Sea - Andrey A. Begun; Yury N. Elkin; Sergey O. Maximov; Ludmila S. Belogurova; Alexander А. Artyukov (Известия ТИНРО)
Feeding of sand dollars Echinarachnius parma and Scaphechinus mirabilis (Clypeasteroida) in the Troitsa Bay, Japan Sea is investigated. Both species dwell on coarse bottom sand with the percentage of fine fraction (< 0.2 mm) no more than 3 %. Diatoms are the most important component of the sand dollars feeding, they are represented by 50 species in the ground but only 27 species in the faeces, with predominance of the cells with chloroplasts in the faeces, that indicates a selectivity of the sand dollars feeding. High similarity (0.97) of algal flora in the faeces of S. mirabilis and E. parma shows their common feeding habits. Crystals of zircon and ilmenite with specific gravity 4.7 g/cm3 are accumulated in the diverticulum of S. mirabilis though they are very rare in sandy grounds.